URGENSI PENGGOLONGAN NARAPIDANA DALAM LEMBAGA PEMASYARAKATAN: Studi di Lembaga Pemasyarakatan Kelas IIB Blangpidie - safarina safarina; Itok Dwi Kurniawan (Universitas Slamet Riyadi, 2024)
Correctional Institutions are places for providing guidance to prisoners and correctional students. The target of implementing the correctional system is basically to realize the goal of correctional institutions, namely to shape correctional inmates into complete human beings, aware of their mistakes, improve themselves, and return to society as good and useful people. Through this correctional system, the training provided to prisoners is more humane while still upholding their honor and dignity as human beings. One of these processes can be seen in efforts to classify prisoners as an idea of criminal individualization in training prisoners based on the correctional system. Guidance and education will be maximized if there is classification of prisoners, based on age, gender, type of crime, length of sentence and so on. This research aims to find out what the procedures are and how important it is to classify prisoners at the class IIB Blangpidie penitentiary. The research method used is an empirical legal approach, where the data obtained is based on direct observations according to what happens in the field. The results of this research indicate that the classification of prisoners in the Class IIB Blangpidie penitentiary is in accordance whit correctional objectives. Keywords: Correctional Institutions, Prisoners, Classification